Hubungan tingkat kecemasan terhadap kualitas hidup pada pasien kanker yang menjalani kemoterapi - Sulastriningsih, Inda; Prasestiyo, Hamudi; Sriyati, Sriyati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Cancer is a chronic disease that affects not only physical health but also patients’ psychological well-being, including anxiety. Cancer patients undergoing chemotherapy frequently experience anxiety due to treatment side effects, uncertainty regarding prognosis, and concerns about disease recurrence, which may ultimately reduce their quality of life. Purpose: To determine the relationship between anxiety levels and quality of life among cancer patients undergoing chemotherapy. Method: This study employed a quantitative approach with a descriptive correlational design using a cross-sectional method. The sample consisted of 47 cancer patients undergoing chemotherapy, selected through purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), while quality of life was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Data were analyzed using the Spearman Rank correlation test. Results: The findings indicated that 34.0% of patients experienced moderate anxiety, and 57.4% had a moderate level of quality of life. The Spearman Rank correlation test showed a significant relationship between anxiety level and quality of life among cancer patients undergoing chemotherapy (p-value = 0.000 [< 0.05]) with a correlation coefficient of −0.792. Conclusion: There is a statistically significant and strong negative correlation between anxiety level and quality of life among cancer patients undergoing chemotherapy. Keywords: Anxiety; Cancer; Chemotherapy; EORTC QLQ-C30; Quality Of Life. Pendahuluan: Kanker merupakan penyakit kronis yang tidak hanya berdampak pada kondisi fisik, tetapi juga memengaruhi aspek psikologis pasien, salah satunya kecemasan. Pasien kanker yang menjalani kemoterapi sering mengalami kecemasan akibat efek samping terapi, ketidakpastian prognosis, serta kekhawatiran terhadap kekambuhan penyakit, yang pada akhirnya dapat menurunkan kualitas hidup. Tujuan: Untuk mengetahui hubungan tingkat kecemasan terhadap kualitas hidup pada pasien kanker yang menjalani kemoterapi. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain deskriptif korelasional dan pendekatan cross sectional. Sampel penelitian ini sebanyak 47 pasien kanker yang menjalani kemoterapi yang dipilih menggunakan teknik purposive sampling. Tingkat kecemasan diukur menggunakan kuesioner Hamilton Anxiety Rating Scale (HARS), sedangkan kualitas hidup diukur menggunakan European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Teknik analisa data menggunakan uji korelasi Spearman Rank. Hasil: Menunjukkan tingkat kecemasan sedang (34%) dan kualitas hidup sedang (57.4%). Uji korelasi spearman rank menandakan adanya hubungan antara tingkat kecemasan terhadap kualitas hidup pada pasien kanker yang menjalani kemoterapi dengan p-value = 0.000 < 0.05 dan koefisien korelasi -0.792. Simpulan: Terdapat hubungan yang signifikan antara tingkat kecemasan terhadap kualitas hidup pada pasien kanker yang menjalani kemoterapi. Kata Kunci: EORTC QLQ-30; Kanker; Kecemasan; Kemoterapi; Kualitas Hidup.